The Concept of Dzikir by Abdul Rauf Singkel in the Tanbih al-Masyi Book - Shodiqul Amin; Susi Ambarwati (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This research portrays the concept of dzikir. In this case, the basis of the researchers' understanding ishow dzikir performed by Abdul Rauf Singkel, a scholar as the founder of Tarekat Syatariyyah (the order of Islamic mysticism of Syattariyah). The teaching of dzikir by Abdul Rauf Singkel is closely related to the teaching of dzikir in Sufism. It can be seen especially in what whe wrote in one of his works, the Tanbih al-Masyih book. The results of this study revealed that the concept of dzikirgiven by Abdul Rauf is an attempt to prevent our selves from negligence and forgetfulness. Dzikir also strengthens the faithfulness andsense of divinity. Abdul Rauf Singkel emphasizes doing dzikir to always remember Allah SWT. In his teaching, he taught dzikir by explaining five kinds of it, namely illa Allah, Allah Allah, huwahuwa, hu Allah hu Allah, Allah hu Allah hu. Furthermore, he also taught two ways of dzikir namely with sir and jahr. Also, he taught dzikir after Fardu prayer, and he encourages to do lots of dzikir to Allah even after doing prayer. Abdul Rauf Singkel also stated that the purpose of dzikir is to acknowledge God, and it can be useful for both physical and mental healers.